NONPROFIT ORGANIZATIONS CONTRIBUTION TO INCREASING THE TRANSPARENCY OF PUBLIC PROCUREMENT IN INDONESIA - Wicaksono, Kristian Widya (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
The aim of this paper is to examine the contribution of Indonesian Corruption Watch (ICW) and the Indonesian Procurement Association or Ikatan Ahli Pengadaaan Indonesia (IAPI) as non-profit organizations to increase the transparency in the public organizations' budgets utilization especially in the procurement of goods and services. In collaboration with the Non-Ministry Government Institutions (LPNK) in Indonesia called the Lembaga Kebijakan Pengadaan Barang/Jasa Pemerintah (LKPP), these non-profit organizations developed "opentender.net" websites to empower the public in monitoring and controlling public procurement by assessing the possibility of corruption. After explaining the background of non-profit contributions, we evaluate the contributions of the ICW and IAPI by using exploratory design to explore the shortcomings of the "opentender.net" website. The result shows that the website could not provide three information details namely the estimated price created by the tender bidders or Harga Perkiraan Sendiri (HPS), the exact amount of value stated in the contract and the market cost. Thus, it hampering the provision of evidence to provide reliable and valid proof of the corruption possibilities.